Ormond's disease - the current state of knowledge about diagnosis and treatment - Dankiewicz, Sara; Bróż, Sebastian; Żelazny, Przemysław; Filipczak, Joanna; Swora, Aleksandra; Borowik, Joanna; Sygacz, Oliwer; Brodowski, Wojciech; Pawłowski, Piotr; Basta-Arciszewska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction: Retroperitoneal fibrosis (Ormond's disease; RPF) is a rare condition characterized by chronic inflammation and resulting progressive fibrosis of the retroperitoneal space. Due to its low prevalence and uncharacteristic symptoms, it is often overlooked in the diagnostic process, resulting in a late-stage diagnosis when complications are already present and treatment options are limited. The aim of the study: The purpose of our study was to present, based on the available literature, the latest reports on the diagnosis and treatment of Ormond disease. State of knowledge: The diagnosis of RPF is based on an anamnesis and imaging. Sometimes a surgical biopsy of the fibrous tissue is necessary. The pathogenesis remains partly unclear. There is no characteristic laboratory marker for early diagnosis of the disease. It is important to distinguish the primary form from the secondary form, in which the trigger factors are known. In therapy, steroid therapy is still the standard. Attempts are being made to treat with other immunosuppressants and biologic drugs with good results, which speaks to the autoimmune basis of the disease. In some cases, surgical treatment and removal of fibrous tissue compressing abdominal structures is essential. Summary: Although the state of knowledge about retroperitoneal fibrosis has been greatly expanded in recent years, many questions remain to be clarified, especially about its pathogenesis and possible early clinical clues to facilitate diagnosis.